Data-Driven SEO Techniques for Strengthening Digital Customer Acquisition - Siti Khoirunnisa (Politeknik Siber Cerdika Internasional, 2025)
This study investigates the implementation of data-driven SEO techniques and their impact on customer acquisition performance across various organizational contexts. Employing a mixed-methods approach, the research combines quantitative survey data from 427 digital marketing practitioners with qualitative insights from 35 in-depth interviews. Data collection utilized stratified random sampling and structured interview protocols, while analysis employed multiple regression, ANOVA, and thematic analysis techniques. Four principal findings emerged: (1) adoption rates vary significantly by organization type, with technology firms and e-commerce companies showing substantially higher adoption (75.4% and 71.2%) compared to B2B organizations (42.7%); (2) analytics tool sophistication demonstrates strong positive correlation with customer acquisition performance, explaining up to 61.2% of variance in conversion rates; (3) balanced strategies integrating on-page and off-page SEO significantly outperform single-focus approaches, achieving 71.8% traffic growth; and (4) five critical success factors were identified including data literacy, cross-functional integration, adaptability, content quality emphasis, and strategic vision. This research advances theoretical understanding by integrating diffusion of innovation theory with dynamic capability perspective, while providing actionable frameworks for practitioners. The study's originality lies in quantifying SEO-performance relationships and revealing that effective implementation requires comprehensive organizational transformation beyond mere technology adoption.